Polycystic ovary syndrome (PCOS), pathophysiology and treatment, a review - Alves , Mariana Luiza Schreiner (2022)
Polycystic ovary syndrome is a pathology of multifactorial etiology and one of the main causes of female infertility worldwide. In addition to changes in reproductive physiology, such as irregular menstrual cycles, anovulation, hyperandrogenism and the presence of multiple ovarian cysts, metabolic changes also occur that can affect the quality of life and survival of women with the syndrome. Endocrine impairment linked to polycystic ovary syndrome occurs due to the development of metabolic syndrome, a condition characterized by impaired glucose tolerance, dyslipidemia and hypertension. However, the manifestation of symptoms associated with polycystic ovary syndrome depends on the interaction between genetic and epigenetic factors, lifestyle and eating habits. The interrelationship between these factors results in the phenotypic diversity presented by women with the syndrome. That is, the clinical manifestations and symptomatic severity vary among the carrier women, so that the treatment is individualized for each patient. The therapeutic management of the syndrome is aimed at symptomatic relief and ovulation induction, since there is still no curative treatment. This narrative review aims to highlight the main clinical, endocrine and metabolic aspects of polycystic ovary syndrome, one of the main causes of female infertility.